2000
DOI: 10.1073/pnas.220402097
|View full text |Cite
|
Sign up to set email alerts
|

Bestrophin, the product of the Best vitelliform macular dystrophy gene ( VMD2 ), localizes to the basolateral plasma membrane of the retinal pigment epithelium

Abstract: Best vitelliform macular dystrophy is a dominantly inherited, early onset, macular degenerative disease that exhibits some histopathologic similarities to age-related macular degeneration. Although the vitelliform lesion is common in the fundus of individuals with Best disease, diagnosis is based on a reduced ratio of the light peak to dark trough in the electrooculogram. Recently, the VMD2 gene on chromosome 11q13, encoding the protein bestrophin, was identified. The function of bestrophin is unknown. To faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
329
1
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(342 citation statements)
references
References 29 publications
8
329
1
2
Order By: Relevance
“…Firstly, in the case of Bestrophins, membrane topology studies showed that Bestrophin1 is localized in the basolateral membrane of the retinal pigmented epithelium [17] . Secondly, the mutation in hBest1 responsible for the disease vitelliform macular dystrophy impairs its calcium-activated chloride channel function [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, in the case of Bestrophins, membrane topology studies showed that Bestrophin1 is localized in the basolateral membrane of the retinal pigmented epithelium [17] . Secondly, the mutation in hBest1 responsible for the disease vitelliform macular dystrophy impairs its calcium-activated chloride channel function [27] .…”
Section: Discussionmentioning
confidence: 99%
“…2,3,6 BEST1 encodes a 585 amino acid transmembrane protein bestrophin-1, located in the basolateral membrane of the retinal pigment epithelium (RPE), 7 and was originally associated with Best vitelliform macular dystrophy (BVMD). 8 We describe the phenotypic variability of ADVIRC in a family with mutations in BEST1 (p.V86M), and report novel ocular associations including iris dysgenesis and optic nerve dysplasia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, only a few studies have investigated Bestrophin protein expression. Immunohistochemisty studies have localized human Bestrophin 1 to the basolateral membrane of the retinal pigment epithelium (23); murine Bestrophin 1 to tracheal and colonic epithelial cells and kidney (4,5); and murine Bestrophin 2 to the basolateral membranes of olfactory sensory neurons, colonic, tracheal, and nonpigmented cilliary epithelial cells (3,5,30). There have been no studies on the tissue and cellular localization of native Bestrophin 3 in any tissue including the heart.…”
mentioning
confidence: 99%